Bearing Wear Line Contact Simulation For Lubricated Surfaces - Tahrin, Muhammad Nizam Naim; Akmal Nizam Mohammed, (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Cylindrical roller bearings have a large radial load capacity and are suitable for accurate and speedy operation. The most bearing of the machines, less than 20% of bearing failures, is not due to improper lubrication. This means that proper lubrication is a must in the machinery industry. This includes not enough lubricant, incorrect lubrication and high temperatures that lower the grade of the lubricant. In order to minimize friction, excess heat and wear, the lubricant film must be included in order to separate the moving parts (Beats, 2005). The main objectives for this project are to analyse roller bearing wear in several lubrication conditions (non-lubricated, grease and lubrication oil). Also to compare simulation result from ANSYS 19.2 software and SOLIDWORKS simulation for the non-lubricated condition. Develop 3D bearing models by using SOLIDWORKS software. Using the non-lubricated, grease and lubrication oil to lubricate the bearing. The loads are constant in magnitude and direction, for radial bearing loads and for thrust bearing axial loads which acts centrically. The parameters such as The rotation speed, lubricant.viscosity (grease = 32 mm2/s, oil = 15 mm2/s) and load is set to 3kg.